On Geodesic Points of 6-Dimensional Hermitian Submanifolds of Cayley Algebra [Articol] - Banaru, Mihail; Banaru, Galina (My University, 2024)
Six-dimensional Hermitian submanifolds of Cayley algebra defined by means of three-fold vector cross products are considered. It is proved that the Weyl tensor of a 6-dimensional Hermitian submanifold of Cayley algebra vanishes at a geodesic point if and only if the scalar curvature at this point also vanishes.
Keywords: geodesic point; Hermitian manifold